Demand for Logistics Management Studies in North Eastern Thailand - Mustakim Melan; Pichit Prapinit; Rohafiz Sabar (International Journal of Supply Chain Management, 2019)
The research investigates the demand on education in the field of logistics management among the high school and vocational students at North Eastern of Thailand. The research explores the needs for labor market in logistics between the private enterprises and government agencies. The surveys were conducted among 830 respondents which include students, entrepreneurs, public and private enterprises through in-depth interviews and brainstorming sessions. The result indicates that the needs for further education among students, mostly female, aged between 19-21 years old. A total of 72.30 %Â Â Â required the logistics disciplines in future businesses (4.31, SD = 0.962). The nature of the curriculum should be focusing on logistics theory (4.35, SD = 0.962). The equation of multiple regressions showed that the logistics education met the labor market (Dem), income level of the parents (inc), distance from home to schools (Dis) and the labor demand in Logistics dropped even at the Northeast. The entrepreneurs and the private sectors indicated to 70 %, 18 %, state agencies, enterprises and other organizations in 12 % which agreed on education for better development in logistics market. Personnel in logistics is critical for the future (4.31, SD = 0.692), demand for logistics in trades border (4.12, SD = 0.798), transportation movement at the Northeast links with neighbouring countries (4.12, SD = 0.798) and personnel logistics with a good command of English (4.01, SD = 0.561). The exhibit shows slightly reduction on logistics trend at the Northeast due to knowledge and education. Logistics shall be the important factors due to growing of business volumes, enhance on its competitiveness and focusing on costs reduction. The government policy was very encouraging towards logistics businesses. The demand for logistics personnel are increasing and this will contribute to the economic growth at the North East. Suggestion for future development is to have a real learning on the logistics theory through government and private partnership. This will enable the best of logistics education towards improvement and quality labor for better economic in Thailand.